Engineering a mevalonate pathway in Halomonas bluephagenesis for the production of lycopene - Su, Qixuan; Cheng, Ping; Sun, Jiyuan; Zhang, Yulin; Zheng, Yang; Jiang, Xiao-Ran; Rao, Xiancai (Frontiers in Microbiology, 2023)
Red-colored lycopene has received remarkable attention in medicine because of its antioxidant properties for reducing the risks of many human cancers. However, the extraction of lycopene from natural hosts is limited. Moreover, the chemically synthesized lycopene raises safety concerns due to residual chemical reagents. Halomonas bluephagenesis is a versatile chassis for the engineered production of fine chemicals because of its open growth property without sterilization. In this study, a heterologous mevalonate (MVA) pathway was introduced into H. bluephagenesis strain TD1.0 to engineer a bacterial host for lycopene production. A pTer7 plasmid mediating the expression of six MVA pathway genes under the control of a phage PMmp1 and an Escherichia coli Ptrc promoters and a pTer3 plasmid providing lycopene biosynthesis downstream genes derived from Streptomyces avermitilis were constructed and transformed into TD1.0. The engineered TD1.0/pTer7-pTer3 produced lycopene at a maximum yield of 0.20 mg/g dried cell weight (DCW). Replacing downstream genes with those from S. lividans elevated the lycopene production to 0.70 mg/g DCW in the TD1.0/pTer7-pTer5 strain. Optimizing the PMmp1 promoter in plasmid pTer7 with a relatively weak Ptrc even increased the lycopene production to 1.22 mg/g DCW. However, the change in the Ptrc promoter in pTer7 with PMmp1 did not improve the yield of lycopene. Overall, we first engineered an H. bluephagenesis for the lycopene production. The co-optimization of downstream genes and promoters governing MVA pathway gene expressions can synergistically enhance the microbial overproduction of lycopene.